PEMBERHENTIAN PRESIDEN REPUBLIK INDONESIA DARI MASA KE MAS - Sunarno - (Wacana Hukum, 2011)
Abstract: The impeachment of the President of Indonesia that has happened from periode to periode is not the same uniform. In the Old Orde has been no provision for sure when the President can be impeach, especially when the President Soekarno was appointed as President for Life. During the New Order, according to Article 4 has been set Tap No.III/MPR/1978 to impeach the President before his term runs out, namely because: (a) at his own request, (b) remain absent, (c) really is agains the GBHN. During the Reformation, the termination of President expressly provided in Article 6 and Article 7 of the 1945 Constitution. Both in the Old Orde  and the New Orde Impeachment of President is more political than judicial. While at the Reformation Orde had never happened to impeach the Presiden. In Constitutional Law, decisions of state institution in generally is more political than judicial. Keywords: Impeachment, The  President  Republic of Indonesia